MODEL KEBIJAKAN PEMERINTAH DALAM PENGEMBANGAN PARIWISATA DI KOTA SAMARINDA - Cathas Teguh Prakoso (Jurnal Paradigma (JP), 2019)
This article aims to describe and analyze the government's policy model to develop the tourism sector in Samarinda. The policy is based on the assumption that the tourism policy of Samarinda has not delivered its potential to increase the tourism sector. This research is descriptive with a qualitative method. Primary data are collected through interviews with both government and non-government informants. Secondary data are collected by screening related regulations and documents and then analyzed by interactive method. The research finds that Samarinda tends to develop metropolitan-based tourism rather than traditional ones, while the policy itself is formulated using the rational model.Keywords: tourism development, public policy model, Samarinda